(untitled) - Hillel, Daniel (New York, 1972)
This book presents papers that were given at a special invitational panel on the topic " Optimizing the soil physical environment toward greater crop yields", convened as part of the international symposium on soilwater physics and technology.
Keywords: Soil physics,Soil science